2020
DOI: 10.1158/1078-0432.ccr-19-2912
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Splice Variant of HYAL-4 Drives Malignant Transformation and Predicts Outcome in Patients with Bladder Cancer

Abstract: Purpose: Poor prognosis of patients with muscle-invasive bladder cancer (BC) that often metastasizes drives the need for discovery of molecular determinants of BC progression.Chondroitin sulfate proteoglycans, including CD44, regulate cancer progression; however, the identity of a chondroitinase (Chase) that cleaves chondroitin sulfate from proteoglycans is unknown. HYAL-4 is an understudied gene suspected to encode a Chase, with no known biological function. We evaluated HYAL-4 expression and its role in BC. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…In this study we utilized empty vector (EV), HYAL-4 Wt (Wt) and HYAL4-V1 (V1) stable transfectants of BC cells (T24, HT1376 and 253J) and an immortalized urothelial cell line (Urotsa). These transfectants, as well as, HYAL-4 shRNA and CD44 siRNA transfectants have been previously characterized (16). All transfectants were cultured in RPMI 1640 plus FBS and gentamicin.…”
Section: Cells and Reagentsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study we utilized empty vector (EV), HYAL-4 Wt (Wt) and HYAL4-V1 (V1) stable transfectants of BC cells (T24, HT1376 and 253J) and an immortalized urothelial cell line (Urotsa). These transfectants, as well as, HYAL-4 shRNA and CD44 siRNA transfectants have been previously characterized (16). All transfectants were cultured in RPMI 1640 plus FBS and gentamicin.…”
Section: Cells and Reagentsmentioning
confidence: 99%
“…We recently discovered the first known example of a eukaryotic chondroitinase (Chase) and demonstrated that it is a driver of malignant BC and a potential prognostic marker for metastasis and BC-specific survival (16). This Chase is encoded by a novel splice variant of HYAL-4, a member of the hyaluronidase family of genes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations